Competition and chaos : U.S. telecommunications since the 1996 Telecom Act - Crandall, Robert W. (Washington, D.C. : Brookings Institution Press, 2005)
"Examines how the 1996 Telecommunications Act and its antecedents have affected the major telecommunications providers and analyzes the act's effect on economic welfare in the United States"--Provided by publisher
Introduction -- Opening telecom markets : the 1996 Telecommunications Act -- The first eight years under the new law -- Local competition under the 1996 act -- Effect of the 1996 act on incumbent local companies -- The death of distance and of the long-distance carriers -- The rapid growth of wireless telecommunications -- The broadband revolution -- Telecom reform in other countries -- A look back and a look forward -- Appendix. estimates of Bell Company cumulative capital expenditures across states, 1996?-2003.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: United States; United States; Telecommunications Act of 1996 (United States); Telecommunication policy -- United States; Telecommunication -- Deregulation -- United States; Competition -- Government policy -- United States; Telecommunication -- Law and legislation -- United States; Télécommunications -- Politique gouvernementale -- États-Unis.; Télécommunications -- Déréglementation -- États-Unis.; BUSINESS & ECONOMICS -- Industries -- Media & Communications; TECHNOLOGY & ENGINEERING -- Telecommunications; Competition -- Government policy -- United States; Telecommunication -- Law and legislation -- United States; Telecommunication policy -- United States; Telecommunication -- Deregulation -- United States; Competition -- Government policy; Telecommunication -- Deregulation; Telecommunication -- Law and legislation; Telecommunication policy; United States